Comparative metagenomic analysis reveals the adaptive evolutionary traits of siboglinid tubeworm symbionts - Liu, Jinyi; Zhou, Yingli; Feng, Jingchun; Cai, Chaofeng; Zhang, Si (Frontiers in Microbiology, 2025)
Tubeworms flourish in marine cold seeps and hydrothermal vents through the establishment of symbiotic relationships with chemosynthetic bacteria. However, the environmental adaptations and evolutionary relationships of tubeworm symbionts across diverse habitats and hosts remain largely unknown. In this study, we characterized the genomes of 26 siboglinid tubeworm symbionts collected from deep-sea hydrothermal vents, cold seeps, and deep-sea mud, including two sequenced in this study and 24 previously published. Phylogenetic analysis classified the 26 symbiont genomes into five distinct clusters at the genus level. The findings highlight the remarkable diversity in symbiont classification, influenced by the habitat and species of tubeworm, with the symbiont genome characteristics of various genera revealing unique evolutionary strategies. Siboglinid symbionts exhibit functional metabolic diversity, encompassing chemical autotrophic capabilities for carbon, nitrogen, and sulfur metabolism, hydrogen oxidation, and a chemoorganotrophic ability to utilize various amino acids, cofactors, and vitamins. Furthermore, the symbiont’s homeostatic mechanisms and CRISPR-Cas system are vital adaptations for survival. Overall, this study highlights the metabolic traits of siboglinid symbionts across different genera and enhances our understanding of how different habitats and hosts influence symbiont evolution, offering valuable insights into the strategies that symbionts use to adapt and thrive in extreme environments.